Exploring the relationships among teacher–student dynamics, learning enjoyment, and burnout in EFL students: the role of emotional intelligence - Li, Ying; Zhang, Li (Frontiers in Psychology, 2024)
Introduction Within the realm of Chinese English as a Foreign Language (EFL) education, this research endeavors to explore the intricate interplay among teacher-student relationships, learning enjoyment, and burnout. It specifically aims to investigate the potential mediation role of emotional intelligence. The study delves into the experiences of 806 EFL students to comprehensively scrutinize these dynamics. Methods Employing Structural Equation Modeling (SEM), this study conducts a thorough analysis of the relationships between teacher-student dynamics, learning enjoyment, and burnout among EFL students. The primary objectives involve uncovering correlations among these factors and elucidating the potential mediating impact of emotional intelligence. Results The findings underscore robust associations between positive teacher-student relationships, heightened learning enjoyment, and reduced levels of burnout among EFL students. Noteworthy is the pivotal role of emotional intelligence, acting as a mediator, offering insights into the intricate ways in which teacher-student relationships and learning enjoyment influence burnout levels. Discussion These outcomes highlight the significance of nurturing students’ emotional intelligence as a protective factor against burnout, advocating for tailored educational interventions. The research advocates for proactive measures to enhance emotional intelligence among EFL students, emphasizing its potential to mitigate burnout. Moreover, it suggests pedagogical strategies and institutional support prioritizing emotional intelligence to foster the well-being and academic success of Chinese EFL students.